DETERMINATION OF THE WELLBEING OF SILVER CATFISH IN DADIN KOWA RESERVOIR - ADAMU UMAR, ZALIHA; ABUBAKAR, KOTOS A.; ADAMU GARKUWA , NURA; ISAH, ZAINAB (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Biomonitoring of the ecological conditions of the aquatic biota and its water quality are the keys for effective management of aquatic ecosystem. Physicochemical parameters and the general wellbeing of Bagrus bayad in Dadin Kowa reservoir were investigated. Water samples were collected from the three sampling stations on biweekly basis for physicochemical analysis. The range of air temperature, water temperature; pH; Transparency; Conductivity; Dissolved Oxygen; Biological Oxygen Demand BOD); Chemical Oxygen Demand (COD); phosphates and nitrate were 28.00±.88 to 33.00±1.00OC; 24.00±0.99 to 28.00±0.58OC; 7.53±.03 to 8.54±0.08; 6.86±0.87 to 10.00±0.28cm; 54.00±1.53 to 122.67±1.67μS/cm; 4.08±0.29mg/L to 6.97±1.27mg/L; 2.15±0.08 to 3.04±0.03 mg/L; 3.66±0.18 to 4.49±0.37 mg/L; 3.51±0.17 to 3.97±0.09mg/L 7.43±.0.23 to 10.20±0.21mg/L, respectively. All the parameters were significantly different between sites and months (p-value ≤ 0.005). Negative allometric growth pattern was observed in male Bagrus bayad (b-values <3) with good condition factor (k-value >1) while positive allometric growth was observed in female Bagrus bayad. The mean condition factor was 1.22±0.77 and 1.04±0.01 for males and females, respectively, indicating that the species are in good physical state of wellbeing in the reservoir. There is need for regular examination of the physicochemical parameters and condition factor of the reservoir across different seasons of the year.